2013
DOI: 10.1371/journal.pone.0064663
|View full text |Cite
|
Sign up to set email alerts
|

Functional Domains of Androgen Receptor Coactivator p44/Mep50/WDR77and Its Interaction with Smad1

Abstract: p44/MEP50/WDR77 has been identified as a coactivator of androgen receptor (AR), with distinct growth suppression and promotion function in gender specific endocrine organs and their malignancies. We dissected the functional domains of p44 for protein interaction with transcription factors, transcriptional activation, as well as the functional domains in p44 related to its growth inhibition in prostate cancer. Using a yeast two-hybrid screen, we identified a novel transcription complex AR-p44-Smad1, confirmed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
(37 reference statements)
1
3
0
Order By: Relevance
“…None of these studies detected direct interaction between AR and p53. Interaction between AR and WDR77 has been shown ( Li et al, 2013 ) and our studies show that WDR77 mediates recruitment of p53 to AR.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…None of these studies detected direct interaction between AR and p53. Interaction between AR and WDR77 has been shown ( Li et al, 2013 ) and our studies show that WDR77 mediates recruitment of p53 to AR.…”
Section: Discussionsupporting
confidence: 71%
“…Despite previous reports of functional interaction between AR and p53 ( Dean and Knudsen, 2013 ; Guseva et al, 2012 ; Cronauer et al, 2004 ; Shenk et al, 2001 ; Gurova et al, 2002 ), these proteins have never been found to interact directly. However, interaction between WDR77 and AR has been described ( Li et al, 2013 ). Therefore, the possibility that p53 and WDR77 interact physically was explored.…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with this observation, overexpression of MEP50 in the nucleus stimulated proliferation and invasion only in the presence of estrogen or androgen [19]. Part of the role of MEP50 in hormone-responsive tumors may be independent of PRMT5, mediated through interaction and recruitment of the Smad1 transcription factor [16]. …”
Section: Introductionmentioning
confidence: 79%
“…P44/WDR77 has been identified as a coactivator of the AR, with distinct growth suppression and promotion function in gender-specific endocrine organs and their malignancies. Instead of the traditional WD40 domain at the C-terminus, it has been shown that the N-terminal region of p44 mediates the interaction between p44, the N-terminus of the AR, and full-length Smad1 (Li et al 2013). P44 is a component of the methylome complex (Friesen et al 2002) suggesting that it functions as a coactivator via supporting methylation (see Table 1).…”
Section: Journal Of Molecular Endocrinologymentioning
confidence: 99%